Proceedings of the 2016 International Conference on Modern Management, Education Technology, and Social Science (MMETSS 2016) 2017
DOI: 10.2991/mmetss-16.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Research on Hot Research Topics on Personalized Learning and Its Development Trend in China:Based on Co-word Visualization Analysis from CSSCI

Abstract: Abstract:With the continuous development and change of the Times, education view is gradually shifted from teachers to students, and personalized learning begins to return to people's horizons.In this paper, based on CNKI, with co-word visualization analysis as research methods, the personalized learning research hot topic and development trend in our country are summarized and analyzed.Research shows that: the personalized learning research hot topics includes data mining, MOOC, learning environment, learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Although monitoring progress has become an area of continued educational interest, as evidenced by the increase in the number of patents filed for related technology, there has also been some skepticism towards SE on the basis of mismatches between the descriptors and students’ own perceptions ( García Sanz, 2020 ). Similarly, a review of the literature shows that personalized learning via technology is highly regarded among educationalists, and is one of the most studied resources for language learning ( Zhou et al, 2016 ), prompting a comparable deluge of patents ( Chao et al, 2009 ). The overwhelming interest in the potential of these tools is what led us to research their effectiveness in the L2 learning process, with the aim of identifying positive common results, and complementarily, areas and aspects for improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although monitoring progress has become an area of continued educational interest, as evidenced by the increase in the number of patents filed for related technology, there has also been some skepticism towards SE on the basis of mismatches between the descriptors and students’ own perceptions ( García Sanz, 2020 ). Similarly, a review of the literature shows that personalized learning via technology is highly regarded among educationalists, and is one of the most studied resources for language learning ( Zhou et al, 2016 ), prompting a comparable deluge of patents ( Chao et al, 2009 ). The overwhelming interest in the potential of these tools is what led us to research their effectiveness in the L2 learning process, with the aim of identifying positive common results, and complementarily, areas and aspects for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…By tracking users’ learning behavior it is able to provide personalized materials more efficiently. According to Zhou et al (2016) , among current areas of research into personalized learning can be found data-mining, massive open online courses (MOOC), the learning environment, learning analysis, ubiquitous learning, learning styles, E-learning, and teaching modes. In like fashion, research into personalized learning models has tended chiefly towards exploring theoretical frameworks, diversification, and the implementation of personalized modes and technology.…”
Section: Research On Language Learning App With Iamentioning
confidence: 99%